The F# Computation Expression Zoo - Petricek, Tomas; Syme, Don (Proceedings of Practical Aspects of Declarative Languages, 2014)
F# computation expressions F# provide a uniform syntax for computations such as monads, monad transformers and applicative functors. The syntax is adaptable and close to built-in language features of Python and C#. This article provides the details shows that the right syntax can often be determined by considering laws.